von Willebrand Factor Multimer Analysis Using a Sensitive Peroxidase Staining Method - Tomita, Yukiharu; Harrison, Janet; Abildgaard, Charles F (Thrombosis and Haemostasis, 1989)
A peroxidase staining method for von Willebrand factor (vWF) multimer analysis was modified for comparison with an autoradiographic method. This method consists of SDS-agarose electrophoresis followed by blotting to a nitrocellulose membrane and a sensitive peroxidase staining method. The resolution of vWF multimers on the nitrocellulose membrane is comparable to that on the conventional autoradiography. Results can be obtained in 3 days. This nonradioisotopic method will be useful for the determination of the type of von Willebrand’s disease in clinical laboratories.
Keywords: von Willebrand factor multimer analysis